Direct cost and healthcare resource utilization of patients with migraine before treatment initiation with calcitonin gene-related peptide monoclonal antibodies by the number of prior preventive migraine medication classes. (4th May 2022) - Foster, Shonda A.; Hoyt, Margaret; Ye, Wenyu; Mason, Oksana; Ford, Janet H.
Abstract: Objective: This study compared all-cause direct cost and healthcare resource utilization (HCRU) among preventive migraine medication (PMM)-naïve patients and patients with up to 3 PMM category switches before initiating calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs). Methods: This was a retrospective analysis of the IBM Marketscan database. Patients who initiated injectable CGRP mAbs between May 2018 and December 2019 (index period) were included in 4 groups based on the number of prior non-CGRP PMM classes used during the 24-month pre-index period: P0 = none; P1 = one; P2 = two; P3 ≥ three. All-cause direct cost and HCRU for groups were compared without adjustment and after generalized propensity score (GPS) matching. Results: Of the 23, 288 patients included (mean age ± standard deviation [SD] 45.4 ± 12.0 years), 85.6% were females, and the mean Charlson Comorbidity Index was 0.69 ± 1.2. P3 group had the highest average annual unadjusted total healthcare costs per patient ($50, 274±$76, 629); the highest costs attributed to procedure/imaging-related expenses ($20, 105±$36, 401) and pharmacy ($11, 633±$29, 763). P0 group had the lowest cost ($25, 288±$41, 427). Pairwise comparison of GPS matched costs showed significantly greater average annual direct costs per patient in the P3 group vs. P0 ( p  = .003), P1 ( p  = .014), and P2 ( p  = .021) groups. GPS matched HCRU also increased with the number of prior PMM classes used. Anti-epileptics (48.9%) were the most commonly used PMM class, with triptans (75.2%) being the most common acute medication class. Conclusions: Total direct healthcare cost and HCRU increased significantly with increasing use of PMM classes with the greatest cost difference existing between the P0 and the P3 groups. PLAIN LANGUAGE SUMMARY: Medications used for the prevention of migraine (PMM) are underused as they might cause adverse effects, intolerance, or may lack efficacy. This leads to the discontinuation of the current treatment and switching to other treatments. Calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs) are a new class of drugs for the prevention of migraine. Since 2018, four CGRP mAbs have been approved for use in the prevention of migraine. It is known that patients who use more preventive migraine treatments incur greater total direct (caused by a number of medical visits or increased healthcare resource utilization, surgery, drugs, equipment, etc.) annual healthcare costs and healthcare resource utilization (HCRU) in patients with migraine. In the current study, the annual average direct cost and HCRU were compared between patients who had not used preventive medicine and patients who had used 1, 2, or ≥3 preventive medicines for migraine before starting CGRP mAbs. We observed that the healthcare costs and HCRU increased with the use of a higher number of preventive medicines for migraine. Patients who started using injectable CGRP mAbs after at least 3 preventive medicines had the highest healthcare costs and HCRU compared with other groups.